Zmienne oblicza innowacyjności zastosowań ICT w dydaktyce językowej - Karczewska, Dorota (Neofilolog, 2010)
The article focuses on the analysis of aspects and qualities perceived as innovative in the context of the most modern information and communication technologies applied in foreign language teaching. The first attempts to implement modern technologies in FLT were definitely innovative, shedding an entirely new light on the FLT methodology. Later, concurrently with the development of information technologies and IT infrastructure, as well as publication of new computer programs and teaching aids, the perception of what is innovative underwent certain transformations. The language teachers’ growing awareness of opportunities offered by those technological novelties, as well as their increasing levels of professionalism and willingness to adapt to the changing conditions, also contributed to those changes. The author of the article attempts to analyze the transformations in the perception of what is innovative in ICT applications, viewing them in the context of actions undertaken in recent decades regarding implementation of modern technologies, as well as in the context of multi-media FLT materials that are being created by teachers themselves.